RASIO KEUANGAN PENGUKUR KINERJA PERUSAHAAN DAN DAMPAKNYA TERHADAP EKSPEKTASI RETURN SAHAM - Yarnest Yarnest (Jurnal Keuangan dan Perbankan, 2012)
This research was intended to know and to describe BUMN firm performance listed at Indonesian Stock Exchange.It measured finance ratios and its impact to expectation return good stock partially and simultaneously.This observational object was corporate BUMN listed at Indonesian Stock Exchange, period 2005-2009. Thisresearch used design ex post facto. Exhaustive observational corporate BUMN listed at Indonesian Stock Exchange(BEI) were 13 firms. Because of little population, the method used was census method. Analysis techniquesused were analysis multiple regression, quiz f and quiz t, data processing by programs Aviews version 6.0. Theresult of observation showed that liquidity ratio, leverage ratio, activity ratio, profitability ratio and stock ratiocould measure simultaneous firm and performance impacted significant to expectation return stock. Activityratio consisted of average collection period and inventory turnover and stock ratio consisted of price earning ratioand book value per share partially impacted significant to expectation return stock. Meanwhile ratio was liquidity,leverage ratio. Profitability ratio partially did not impact significantly to expectation return stock. Stock ratiomeasured by book value per share constituting impacted as the dominant factor on exspectation return stock.